INVESTMENT ACTIVITY AND INVESTMENT SECURITY - Ismailova Nasiba Komildjanovna (European Science Publishing, 2025)
This article is devoted to socioeconomic aspects of investment security, investment security indicators, economic theories on investment security, criteria for evaluating the investment climate, and issues of providing investment security in the Republic of Uzbekistan.
Keywords: financial globalization, investment, foreign investment, investment attractiveness, economic security, investment security, investment security indicators, external debt of the country, macroeconomic stability, capitalization level of banks, investment in fixed capital, domestic investment, tax burden, investment volume, inflation rate.